52.5k views
4 votes
F(x) = x^2 + 1

g(x) = 5 - x
(f+g)(x) = ?
A. X^2 + x - 4
B. X^2 + x + 4
C. X^2 - x + 6
D. X^2 + x +6

F(x) = x^2 + 1 g(x) = 5 - x (f+g)(x) = ? A. X^2 + x - 4 B. X^2 + x + 4 C. X^2 - x-example-1
User Jaredsmith
by
5.6k points

1 Answer

5 votes

Answer:


x^(2) - x + 6

Explanation:


(f+g)(x) = (x^(2) + 1) + (5 - x) = x^(2) - x + 6


x^(2) has no common term so it's by itself, and so is - x.

The 1 and 5 will be added to get six.

To get the (f + g), you have to add both equations given.

User Mke Spa Guy
by
4.7k points